2012
DOI: 10.1161/circresaha.112.266478
|View full text |Cite|
|
Sign up to set email alerts
|

Revascularization of Ischemic Skeletal Muscle by Estrogen-Related Receptor-γ

Abstract: Rationale Oxidative myofibers in the skeletal muscles express high levels of angiogenic factors, have dense vasculature, and promptly revascularize during ischemia. Estrogen-related receptor-gamma (ERRγ) activates genes that govern metabolic and vascular features typical to oxidative myofibers. Therefore, ERRγ-dependent remodeling of the myofibers may promote neoangiogenesis and restoration of blood perfusion in skeletal muscle ischemia. Objective To investigate the muscle fiber type remodeling by ERRγ and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 49 publications
5
75
1
Order By: Relevance
“…Frozen muscle sections were processed for immunofluorescence staining of capillaries [using CD31/PECAM-1 antibody # RM5200 (Invitrogen)] and of myosin heavy chains (MyHC) type IIA, IIX and IIB [using, respectively, # SC-71, # BF-F3, and # 6H1 (Developmental Studies Hybridoma Bank)], as we previously described [19,20]. All primary antibodies were visualized using suitable Alexa Fluor® or Cy5 secondary antibodies from Molecular Probes.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen muscle sections were processed for immunofluorescence staining of capillaries [using CD31/PECAM-1 antibody # RM5200 (Invitrogen)] and of myosin heavy chains (MyHC) type IIA, IIX and IIB [using, respectively, # SC-71, # BF-F3, and # 6H1 (Developmental Studies Hybridoma Bank)], as we previously described [19,20]. All primary antibodies were visualized using suitable Alexa Fluor® or Cy5 secondary antibodies from Molecular Probes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in many transgenic mouse models, an increase in muscle mitochondrial oxidative capacity is associated with a shift to a more oxidative muscle fibertype composition. For example, mice with musclespecific overexpression of PGC-1a, PGC-1b, PPARd, or ERRg have increases in type I, IIa, or IIx fibers, at the expense of IIb fibers (with each transgenic model showing distinct patterns of fiber-type composition) (20)(21)(22)(23)(24)63). Some of these mouse models also show decreases in fiber cross-sectional area, consistent with a switch to more oxidative fibers (21,23).…”
Section: Ckmt2 Glut4 Cpt1b Fabp3mentioning
confidence: 96%
“…A growing body of evidence suggests that ERRγ is relevant to vascular pathophysiology, including angiogenesis and restoration of blood perfusion in ischemic tissues. 21,22 Here, we provide another pathophysiological function for ERRγ in the process of vascular calcification. Because a previous study reported that ERRγ negatively regulates BMP2-induced osteoblast differentiation and bone formation, we initiated this study with the expectation that ERRγ would have beneficial effects on vascular calcification under calcificationprone conditions.…”
mentioning
confidence: 95%